2018
DOI: 10.1002/bmc.4331
|View full text |Cite
|
Sign up to set email alerts
|

A reliable LC‐MS/MS method for the quantification of N‐acetyl‐p‐benzoquinoneimine, acetaminophen glutathione and acetaminophen glucuronide in mouse plasma, liver and kidney: Method validation and application to a pharmacokinetic study

Abstract: A rapid, specific, and sensitive liquid chromatography-tandem mass spectrometry (LC-MS/MS) method has been developed and validated to simultaneously quantify N-acetyl-p-benzoquinoneimine (NAPQI), acetaminophen-glutathione (acetaminophen-glut) and acetaminophen-glucuronide (acetaminophen-gluc) in mouse plasma, liver and kidney homogenates. Analytes were eluted by a binary gradient mobile phase composed of water (phase A) and methanol containing 0.1% formic acid (phase B) at a flow rate of 0.3 mL/min, which was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The plasma concentrations in our study were similar. Previous studies in rats and humans have found that the major metabolites of paracetamol are paracetamol-sulphate [27] [28] and paracetamol-glucuronide [23] [25] [29]. Thirty minutes after administration maternal plasma paracetamol-sulphate was twice the concentration of paracetamol-glucuronide, which was 3-fold higher than un-metabolised paracetamol (Tables 2 and 3).…”
Section: Discussionmentioning
confidence: 92%
“…The plasma concentrations in our study were similar. Previous studies in rats and humans have found that the major metabolites of paracetamol are paracetamol-sulphate [27] [28] and paracetamol-glucuronide [23] [25] [29]. Thirty minutes after administration maternal plasma paracetamol-sulphate was twice the concentration of paracetamol-glucuronide, which was 3-fold higher than un-metabolised paracetamol (Tables 2 and 3).…”
Section: Discussionmentioning
confidence: 92%
“…5 Thus, the monitoring of POM in human serum, sweat, and water bodies are important for both human health and controlling environmental poisoning. 5 Numerous techniques such as high performance liquid chromatography, 6 UV spectrophotometry, 7 chemiluminescence 8 and titrimetry, 9 electrophorosis, 10 LC-MS 11 GC-MS 12 and flow injection 13 are available for the detection and determination of POM. Unfortunately, these techniques have several drawbacks and restrictions, such as being expensive and time-consuming.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a variety of analytical tools have been developed for the quantification of ACAP in human fluids and pharmaceutical preparations such as LC-MS, 11 GC-MS, 12 HPLC, 13 spectrofluorometry, 14 chemiluminescence, 15 titrimetry, 16 and flow-injection 17 and FT-IR spectrophotometric analysis. 18 These methods are relatively expensive and time-consuming, require presample preparation, and have very complicated handling procedures.…”
Section: ■ Introductionmentioning
confidence: 99%